Edukasi Orang Tua tentang Pentingnya Literasi Bahasa dalam Mencegah Perundungan dan Membangun KarakterEdukasi Orang Tua tentang Pentingnya Literasi Bahasa dalam Mencegah Perundungan dan Membangun Karakter - Sinta Wahyuni; Silvia Reza Cintya; Indri Juariah; Chelsea Divi Putri; Najmi Hayati (Kilau Publishing, 2025)
Low levels of children’s language literacy are closely related to the limited involvement of parents in providing literacy stimulation at home. This community service program aimed to enhance parents’ awareness and understanding of the importance of language literacy for children’s cognitive and communication development. The activity was conducted using an educative–participatory approach through counseling sessions, interactive discussions, and guidance on simple literacy practices at home. The results showed an increase in parents’ knowledge, positive attitudes, and active participation in supporting children’s literacy development. This program contributes to strengthening family-based literacy practices and fostering a supportive environment for children’s language and character development.